Conversion in Germany - Liesen, Frank (Peter Lang International Academic Publishers, 2023)
Evangelical mission work in Germany has made little inroads to reach secular people with the Good News of Jesus Christ. This book investigates diffusional patterns that enabled three evangelical church plants to guide converts through processes of transformational conversion. Each church plant in this multi-case study represents a salient expression of their correlating missional movement pointing to contemporary trends in German evangelicalism: Migrant missions, new Pentecostal churches, and American mission efforts in conjunction with globally active church planting organizations.